A comparative study on behavior, awareness and belief about cervical cancer among rural and urban women in Vietnam. - Minh Tung Phung; Pham Le An; Nguyen Nhu Vinh; Hong H T C Le; Karen McLean; Rafael Meza; Bhramar Mukherjee; Alice W Lee; Celeste Leigh Pearce (Public Library of Science (PLoS), 2023)
Cervical cancer is the second most common gynecologic cancer in Vietnam but based on the literature, only ~25% of Vietnamese women reported ever being screened for cervical cancer. To inform strategies to reduce the cervical cancer burden in Southern Vietnam where disease incidence is higher than the national average, this study examined behaviors, awareness, barriers, and beliefs about cervical cancer screening among rural and urban women in this geographical region. In October-November 2021, we conducted a cross-sectional study among 196 rural and 202 urban women in Southern Vietnam; participants completed a cervical cancer screening questionnaire. Descriptive analyses and rural-urban differences in screening behavior, awareness, barriers, and beliefs are presented. About half of the rural and urban participants reported ever being screened for cervical cancer. Most participants showed high perceived severity of cervical cancer and benefits of screening. Further, they reported that they would screen if it was recommended by doctors and/or friends/family. However, most women showed low awareness and perceived susceptibility to cervical cancer. Logistical and psychosocial barriers to physician-based screening methods were reported. Based on our results, the World Health Organization 2030 goals for cervical cancer screening are not currently met in Southern Vietnam. Increasing health literacy and engaging doctors and family members/social networks emerged as important avenues to improve screening. HPV (Human papillomavirus) self-sampling is also a potential approach to increase uptake of cervical cancer screening given the identified psychosocial and logistical barriers.